2015
DOI: 10.1159/000434758
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study to Evaluate the Efficacy of a Preoperative Respiratory Rehabilitation Program to Prevent Postoperative Pulmonary Complications after Esophagectomy

Abstract: Background/Aims: Patients with postoperative pulmonary complications after esophagectomy often have increased mortality. The purpose of the study was to examine the efficacy of preventing postoperative pulmonary complications by an intensive preoperative respiratory rehabilitation (PR) program for esophageal cancer patients. Methods: This study was a prospective randomized controlled study. Thirty patients in the PR group and 30 patients in the no preoperative respiratory rehabilitation (NPR) group were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 23 publications
0
92
0
Order By: Relevance
“…Ulinastatin prevents postoperative complications and immunosuppression in esophagectomy patients, thereby prolonging RFS 78. Yamana et al 79. have shown that an intensive preoperative respiratory rehabilitation program can reduce postoperative pulmonary complications in esophageal cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Ulinastatin prevents postoperative complications and immunosuppression in esophagectomy patients, thereby prolonging RFS 78. Yamana et al 79. have shown that an intensive preoperative respiratory rehabilitation program can reduce postoperative pulmonary complications in esophageal cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Despite an increasing number of studies confirming that PR is an effective treatment for improving exercise tolerance, reducing dyspnea, and improving QoL (6,(10)(11)(12)(13), there remains a lack of a standard procedure or practical guidance for LC patients, and few studies have explored the effect of a combined short-term and high-intensity rehabilitation program for preoperative LC patients. These reasons provide the strongest evidence to support the use of IMT and CRT as a combined intervention for PR, and we hypothesize that the combined high intensity program would have a better effect in terms of reducing PPCs than traditional regimens with IMT alone.…”
Section: Discussionmentioning
confidence: 99%
“…In our department breathing and coughing exercises were recommended for the possible atelectasis on POD 1. 16 Also, the exercises might force air that left in the thoracic cavity at the end of the operation leak via the large ''tunnel,'' causing subcutaneous emphysema of the face and neck. This might be the likely explanation of the development of subcutaneous emphysema in our patients.…”
Section: Thoracoscopic Esophagectomy: Early Chest Tube Removalmentioning
confidence: 99%